Buffalo milk composition, processing factors, whey constituents recovery and yield in manufacturing Mozzarella cheese - Sales, Danielle Cavalcanti; Rangel, Adriano Henrique do Nascimento; Urbano, Stela Antas; Tonhati, Humberto [UNESP]; Galvão Júnior, José Geraldo Bezerra; Guilhermino, Magda Maria; Aguiar, Emerson Moreira; Bezerra, Maria de Fátima (FapUNIFESP (SciELO), 2018)
Mozzarella cheese is typically from Italy and consumed in the whole world. The aim of this study was to characterize the manufacture of Mozzarella produced similarly to Italian in a Brazilian dairy industry regarding the milk composition usage, factors involved in the production process, use of raw materials and cheese yield. Was monitored the Mozzarella yield (MY), milk composition, manufacturing of Mozzarella cheese and recovery of whey constituents of 30 lots of Mozzarella cheese in a dairy brazilian industry. Overall, processing reached an adequate MY for this type of cheese, being below 5.0 L kg-1. We find values of 5.93 ± 1.87; 34.97 ± 2.70; 33.39 ± 2.85; 95.04 ± 4.18; 44.02 ± 2.00; and 66.82 ± 3.36 respectively for recovery of fat, protein, casein, lactose, total solids and solids-not-fat in whey. The milk used by the dairy industry had satisfactory physicochemical characteristics. The manufacturing of Mozzarella cheese was efficient.
Keywords: Bubalus bubalis; Dairy; Efficiency; Industry; Pasta-filata